Metacognitive Reading Strategies to Enhance Students' Reading Comprehension in The First Harry Potter Novel' Synopsis "Harry Potter and The Philosopher's Stone (2001)” In Tutoring of Official School at Master Plato College (MPC) - Manik, Kresna Ningsih; Husein, Rahmad; Nasution, Jamaluddin; Sembiring, Yenita Br; Yunanda, Fachri (The Eastasouth Journal of Learning and Educations, 2024)
Reading comprehension means extracting necessary information from a written text as efficiently as possible, rejecting unnecessary information and quickly finding what one is looking for. The main purpose of the writer in this study is to improve the student’s reading skill of Students at the third grade in official school tutoring Master Plato College. This gist of activity in this study is to focuses on how to understand the text, get the essential and detail information from the synopsis of the first harry potter film “Harry Potter and The Sorcerer’s stone (2001)”, there 12 students in this class which consisting of 8 female students and 14 male students, so the total of the students is 22 students. There are some benefits and significances of using metacognitive reading strategies in fostering reading success such as 1) Enhanced Comprehension and Retention, 2) Improved Problem-Solving Skills, 3) Increased Reading Engagement and Motivation, 4) Transferability of Skills. Metacognitive reading strategies help the students learn independently and enhance students' ability to make sense of, monitor, and understand text and evaluate the text they read. Metacognitive Reading Strategy helps students control their thinking while reading. Metacognitive reading strategies play a vital role in fostering reading success by improving comprehension, retention, critical thinking skills, problem-solving abilities, and overall engagement with the text.